Clinical and upper airway characteristics of 3715 patients with the Omicron variant of SARS-Cov-2 in Changchun, China - Jichao Sha; Cuida Meng; Jing Sun; Liwei Sun; Rui Gu; Junzhi Liu; Xuewei Zhu; Dongdong Zhu (Elsevier, 2023)
Objective: The spread of the novel SARS-Cov-2 variant Omicron created a challenging public health situation in a number of countries. In March 2022, Omicron emerged in Changchun, China, and the number of patients infected rapidly increased. The prevalence of Omicron infection symptoms differs from that of Delta, with more upper airway clinical symptoms apparent. This study aimed to investigate the clinical and upper airway characteristics of the Omicron variant. Materials and methods: In this retrospective study, we collected data from participants in Changchun who had tested positive for Omicron with quantitative polymerase chain reaction between 10 March and 30 May 2022 using telephone interviews. The questionnaire was designed by the research team based on the number of upper airway symptoms using the visual analogue scale. We also considered age, sex, vaccination status, general symptoms, and cure period. Results: A total of 3715 patients (2056 males and 1659 females) with mild COVID-19 from the Omicron variant were included. The patients had a mean age of 38.63 ( ± 13.97) years (range 2-86 years). The vaccine uptake rate was 91.33 % (8.66 %, 4.58 %, 65.33 %, and 21.43 % had received zero, one, two, and three doses, respectively). The incidence of upper airway symptoms, including throat and nasal symptoms, was 54.21 %. Throat symptoms were the most common during Omicron infection (49.12 %). Nasal symptoms were also common (20.08 %). The incidence of lower airway symptoms was 25.60 %, and gastrointestinal symptoms was 10.87 %. The incidence of general symptoms was 55.26 %. The cure period ranged from three to 37 days, with a mean of 10.24 ± 4.69 days. We compared the upper airway symptom severity for Omicron among different vaccination statuses and found no differences. Conclusions: The main clinical characteristics of the SARS-Cov-2 Omicron variant are upper airway symptoms and general symptoms. Fever remains the most common symptom, followed by mild dry cough. There was no association between Omicron infection and COVID-19 vaccines, and the vaccination status might have been ineffective against upper airway symptom severity by Omicron.